The use of a digital platform for the development of an inclusive educational environment - Абаева, Галия; Исалиева, Сауле; Алимович, Соня; Бутабаева, Лаура (Pedagogy and Psychology, 2023)
The article describes an experimental study of the effectiveness of the use of multimedia technologies in the correctional and pedagogical process of teaching children with intellectual disabilities. In the analysis of theoretical provisions, much attention is paid to the correctional and developmental possibilities of multimedia, it is said that the unique features of multimedia technologies, such as interactivity, flexibility, multi-channel, personal orientation, can be very useful for individualization and improving the quality of education for children with intellectual disabilities. In order to test the effectiveness, a study was conducted on the example of the development of some of the most important cognitive skills for this category of children (thinking, memory, attention) using the example of correctional and developmental activities. The results of the experiment confirmed the above assumptions and helped to identify the pedagogical conditions for the use of multimedia technologies in working with younger students with mild impairments and intellectual development.